Bilateral synchronous papillary renal neoplasm with reverse polarity and renal cell carcinoma with fibromyomatous stroma: a case report and review of the literature - Chen, Guiwu; Liao, Xiaomin; Liu, Wenqin; Meng, Jiaxin; Li, Yuting; Leng, Xiaoling (Frontiers in Oncology, 2025)
BackgroundThis report presents an exceptionally rare case of bilateral synchronous renal tumors comprising papillary renal neoplasm with reverse polarity (PRNRP) and renal cell carcinoma with fibromyomatous stroma (RCC-FMS) in a single patient. No prior cases of this specific combination occurring synchronously and bilaterally have been reported.Case presentationA 65-year-old man presented with incidentally detected bilateral renal masses. Abdominal ultrasound and contrast-enhanced computed tomography (CT) revealed distinct imaging characteristics for each tumor. The right kidney mass was exophytic, heterogeneous, and hypovascular on ultrasound, showing marked heterogeneous enhancement with hypoenhancing foci on CT. The left kidney mass was a well-circumscribed, mixed-attenuation nodule with peripheral/septal enhancement on CT. The patient underwent bilateral laparoscopic partial nephrectomy. Histopathological and immunohistochemical analysis confirmed PRNRP in the right kidney (CK7+, GATA3+, Ki-67 approximately 2%) and RCC-FMS in the left kidney (PAX-8+, CA IX+, CD10+, Ki-67 approximately 3%). Real-time quantitative-PCR testing was positive for a KRAS exon 2 mutation, but was negative for NRAS (exons 2-4) and BRAF V600 (exon 15) mutations.ConclusionThis represents the first documented case of synchronous bilateral occurrence of PRNRP and RCC-FMS. It highlights significant diagnostic challenges due to overlapping imaging features with more common renal tumors. It underscores the critical role of multimodal imaging (ultrasound, CT) combined with meticulous histopathology, immunohistochemistry, and molecular genetic analysis for accurate diagnosis. The generally indolent nature of both tumors supported successful nephron-sparing surgical management. This unique case emphasizes the need for a high index of suspicion for rare tumor subtypes and a multidisciplinary approach to optimize the diagnosis and tailored treatment of complex renal masses.